Studi perilaku pengelolaan sampah di Kapanewon Mlati, Kabupaten Sleman - Hardito, Muhammad Eko; Pitoyo, Agus Joko; Rahardjo, Noorhadi (Jurnal Pengelolaan Lingkungan Berkelanjutan (Journal of Environmental Sustainability Management), 2024)
Human activities can produce solid waste called garbage. The potential for waste generation in Kapanewon Mlati, Sleman Regency is large, it can reach 60.55 tonnes/day. This study aims to determine the sources and types of waste, methods of waste disposal and management in the community, and then formulate a community-based waste management strategy. The method used in this study is a survey research method that emphasizes survey methods that emphasize primary data surveys and is complemented by secondary data. The results showed that the most common types and sources of waste that occurred at the study sites were food waste and plastic. The method of disposing of waste in the three activities, be it settlements, the economy or offices, is mostly used as a container for trash and/or plastic and then disposes of it in a certain place. The majority of waste management still uses a collection and transportation system with third parties. There are still a few settlements that have waste management institutions and/or movements.